2014
DOI: 10.3892/or.2014.3200
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of fibroblast growth factor receptor 2IIIb enhances the chemosensitivity of human prostate cancer cells

Abstract: Abstract. Fibroblast growth factor receptor 2 (FGFR2) is thought to mediate an important signaling pathway between prostate epithelial cells and stromal cells for maintenance of homeostasis in normal prostate tissue. Abnormalities of FGFR2 have been shown in advanced prostate cancer or prostate cancer cell lines, and we previously demonstrated the tumor-suppressive effects of the restoration of FGFR2IIIb in prostate cancer cells. The aim of the present study was to determine whether FGFR2IIIb plays a role in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…This is an interesting phenomenon but was in contrast with other observations, at which serum-depletion might induce cell apoptosis or enhance chemosensitivity [ 38 ā€“ 40 ]. However, several literatures implied the growth factors or receptors promoted or involved in cell apoptosis [ 41 ā€“ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is an interesting phenomenon but was in contrast with other observations, at which serum-depletion might induce cell apoptosis or enhance chemosensitivity [ 38 ā€“ 40 ]. However, several literatures implied the growth factors or receptors promoted or involved in cell apoptosis [ 41 ā€“ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, expression of dnFGFR2 potentiates the development and progression of prostatic intraepithelial neoplasia (PIN) lesions induced by expression of ectopic FGFR1 kinase, demonstrating the cooperation between ablation of resident FGFR2 and expression of ectopic FGFR1 in promoting PCa progression (Jin et al, 2003; Wang et al, 2004). Restoration of FGFR2IIIb in human PC cells increases the sensitivity to chemotherapeutic reagents (Shoji et al, 2014) and in stromal cells derived from the DT3327 rat PCa model restores the interaction between PCa and prostate stromal cells (Feng et al, 1997).…”
Section: The Intrinsic Stroma-to-epithelium Fgf7/10-fgfr2 Signaling Amentioning
confidence: 99%
“…Whilst these studies in mouse models of prostate cancer have revealed potential novel roles for FGF10 in androgen signaling, it is important to note that elevated FGF10 has not been detected in human prostate cancer tissue ( Abate-Shen and Shen, 2007 ; Eiro et al, 2017 ) and levels of FGF10 in the normal adult prostate are extremely low, compared to those of FGF7 ( Ropiquet et al, 2000 ). Transfection of malignant prostate tumor cells with FGFR2b cDNA has been shown to reduce the growth rate of the derived tumors ( Feng et al, 1997 ) and restoration of FGFR2b expression in castration-resistant prostate cancer cells increased sensitivity to chemotherapeutic agents ( Shoji et al, 2014 ). Further investigation is therefore required to fully elucidate the complex roles of FGF10-FGFR2b signaling in prostate tumourigenesis.…”
Section: Fgf10 In Prostate Cancermentioning
confidence: 99%